Design, Synthesis, and Pharmacological Screening of Novel Porphyrin Derivatives - Ahmed A. Fadda; Rasha E. El-Mekawy; Ahmed El-Shafei; Harold S. Freeman; David Hinks; Manal El-Fedawy (Journal of Chemistry)
A series of porphyrin derivatives 2a–f was synthesized, namely, 5,10,15,20-mesotetrakis[p-methoxyphenyl]-21H,23H-porphyrin (2a), 5,10,15,20-mesotetrakis[2,6-dichloro-phenyl]-21H,23H-porphyrin (2b), 5,10,15,20-mesotetrakis[4-hydroxy-3,5-dimethoxyphenyl]-21H,23H-porphyrin (2c), 5,10,15,20-mesotetrakis[3,4-dimethoxyphenyl]-21H,23H-porphyrin (2d), 5,10,15,20-mesotetrakis[2,4-dichlorophenyl]-21H,23H-porphyrin (2e), and 5,10,15,20-mesotetrakis[3,4,5-trimethoxyphenyl]-21H,23H-porphyrin (2f), in high yields using a new method via a capping mechanism. These dyes were used as a model to study the free radical-induced damage of biological membranes and the protective effects of these porphyrins. It was demonstrated that these dyes were effective in the inhibition of the free radical-induced oxidative haemolysis of rat blood cells. Dyes 2d and 2f which bear methoxy functionality exhibited markedly higher antihaemolysis activity than the other analogs. Molecular modeling methods using ZINDO/INDO-1, with a configuration interaction of 26, and TD-DFT using the energy functional B3LYP and the basis set DGTZVP were used to study the vertical electronic excitations of porphyrins 2a–f and it was shown that the calculated using TD-DFT method was in excellent agreement with the experimental results, while the ZINDO method was inferior. Moreover, excellent correlation between the LUMO energy and cytotoxicity of dyes 2a–f was found.